Leptathanas powelli gen. nov., sp. nov, a new infaunal alpheid shrimp associated with upogebiid mudshrimps in Nigeria (Crustacea, Decapoda) - de Grave, S.; Anker, A. (Zootaxa, 2008)
A new alpheid shrimp genus and species is described from the Niger delta in Nigeria. Leptathanas powelli gen. nov., sp. nov. appears to be associated “commensally” with burrows of mudshrimps, Upogebia furcata (Aurivillius, 1898) (Thalassinidea, Upogebiidae). Leptathanas gen. nov. is superficially similar to Leptalpheus Williams, 1965, a genus composed exclusively of infaunal species. However, it is more closely related to a generic complex around Athanas Leach, 1814, and in particular to Athanopsis Coutière, 1896. The main diagnostic features of Leptathanas gen. nov. are the presence of an articulated plate on the sixth pleonite; the frontal margin of the carapace with a very short rostral projection and without orbital teeth; the asymmetrical and unequal chelipeds carried folded, with the propodus fitting in a ventral excavation of the merus; and the presence of stout cuspidate setae on the protopod of the uropod.